1986
DOI: 10.1128/iai.54.1.207-212.1986
|View full text |Cite
|
Sign up to set email alerts
|

Organization of genes encoding two outer membrane proteins of the Lyme disease agent Borrelia burgdorferi within a single transcriptional unit

Abstract: OspA and OspB are major outer membrane proteins and antigens of the Lyme disease spirochete, Borrelia burgdorferi. We examined the organization of ospA and ospB, the genes encoding these proteins. The location and direction of transcription of each osp gene was determined by subcloning, deletion analysis, and transposon Tn5 mutagenesis. Transposon Tn5 insertions within the ospA gene abrogated expression of ospB, suggesting that these genes are transcribed from a common promoter. Northern blot analysis of mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 36 publications
1
46
0
1
Order By: Relevance
“…Previous mapping studies had indicated that the ospA gene was at the 5' end of the operon and that ospB was located downstream of ospA (Howe etal., 1986). To our knowledge, ospA and ospB are the first genes sequenced from the genus Borrelia and the data strongly support the suggestion by Howe et al, (1986) that the two genes are organized into an operon. The nucleotide sequence of the ospA-ospB operon and flanking regions together with the deduced amino acid sequence of the ospA and ospB gene products are shown in Fig.…”
Section: Dna Sequence Anaiysis Of the Osp Operonsupporting
confidence: 83%
“…Previous mapping studies had indicated that the ospA gene was at the 5' end of the operon and that ospB was located downstream of ospA (Howe etal., 1986). To our knowledge, ospA and ospB are the first genes sequenced from the genus Borrelia and the data strongly support the suggestion by Howe et al, (1986) that the two genes are organized into an operon. The nucleotide sequence of the ospA-ospB operon and flanking regions together with the deduced amino acid sequence of the ospA and ospB gene products are shown in Fig.…”
Section: Dna Sequence Anaiysis Of the Osp Operonsupporting
confidence: 83%
“…Extractions of total DNA and plasmid-enriched DNA from the borrelias, standard agarose dectrophoresis, Southern blot analysis, and direct gel hybridization of low-percentage agarose gels were performed as described previously (22,30,48,49). The probes for the ospA and ospB genes of HIB19 and B31 were recombinant plasmids pTRH43 and pTRH46, respectively (50)(51)(52). The probe DNA was labded with ol-[32p]dATP by nick transhtion using a commercial kit (Bethesda Research Laboratories, Gaithersburg, MD).…”
Section: Methodsmentioning
confidence: 99%
“…We and others demonstrated previously that a single copy of this locus containing these two genes is located on the spirochete's chromosome [1,10]. The genes encoding OspA and OspB of B. burgdorferi are encoded by a single transcriptional unit [11,12]; however, this locus is located on the 49-53-kb linear plasmid having covalently closed ends [13]. The ospD gene is also located on a different linear plasmid of approximately 38 kb [9] while the ospC gene has been mapped recently to a 26-27-kb circular plasmid [14,15].…”
Section: Consensus Sequences (Cons) Are Also Shown Dots Indicate Gapmentioning
confidence: 96%